Aquaria flushing technique of rosella extract (Hibiscus sabdariffa Linn) to determine the value of SGOT and SGPT in milkfish (Chanos chanos) induced by heavy metals (Hg) - Intan Permatasari Hermawan; Olan Rahayu Puji Astuti Nussa; Ady Kurnianto (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The purpose of this study was to determine the value of SGOT and SGPT in milkfish induced by heavy metals (Hg) by aquaria flushing technique with Rosella (Hibiscus Sabdariffa Linn) extract. The samples used were 30 male adult milkfish divided into 5 groups. The treatment group was induced with a toxic dose of heavy metal mercury (Hg), which was dissolved in a volume of m3 of water. Blood collection from the heart vein of milkfish as much as 1-2 ml for SGPT and SGOT examination was carried out using the Berthelot method. The liver, gills and brain of milkfish were then examined, 300 grams were centrifuged until smooth and then dissolved in methanol to obtain concentrations of 25ppm, 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 9 00ppm. and 1000ppm then analyzed by ANOVA. Based on the research results of black roselle flower extract therapy with aquaria flushing system on male milkfish, the average value of SGOT and SGPT showed a very significant decrease in groups P1, P2, P3, and P4, against the P0 group or control group (P<0, 01 ).